Effect of steel slag acting as dewatering agent on the subsequent pyrolysis properties of sewage sludge. (20th November 2022) - Han, Yi; Guo, Mengxin; Xu, Zhibing; Fu, Tianming; Li, Fasong; Huang, Xiaoding; Liu, Nian; Chen, Zongwu; Wang, Teng
Abstract: Steel slag (SS) is used as conditioner to enhance raw sludge (RS) dewaterability successfully. Indeed, SS additive influences the subsequent disposal process. This study evaluates the effect of SS additives on subsequent pyrolysis of RS. The pyrolysis characteristics, gaseous products, and kinetics of RS-SS mixtures were investigated using thermogravimetry and mass spectrometry. The corresponding adsorption capacity of biochar to tetracycline was also discussed. Results indicated that the SS introduction inhibits the pyrolysis reaction of RS. The comprehensive pyrolysis index (CPI) decreased from 6.5 10 −13 /min 2 ·°C 3 to 4.84 10 −13 /min 2 ·°C 3 with SS addition. The main gas products are C2 H3 N, C2 H2 and CO2 during pyrolysis of RS-SS mixtures, occupying >90% of the total gas. Based on Starink and Criado model, the average E values increased with the increasing SS dose and the kinetics was controlled by diffusion (D3) model. Generally, SS component processes duality to RS pyrolysis, namely, it catalyzes the generation of CH4 and adsorbs gas products, simultaneously. Among adsorption (inhibition action) plays a dominated role during pyrolysis. In addition, 10 mg/g SS addition helps to create a RS-biochar with thermal stability and remarkable adsorption to tetracycline (19.18 mg/g). The adsorption effect was codetermined by the interaction (aromatic rings and tetracycline) and proper pore structure. Graphical abstract: Image 1 Highlights: Effect of SS conditioner inhibited the subsequent RS pyrolysis progress. The adsorption of SS component to gas products explained the inhibition. Biochar derived from RS-SS mixture had excellent adsorption to tetracycline. The authors declared that they have no conflicts of interest to this work.